Kampanye Konsumsi Tablet Tambah Darah untuk Kesehatan Remaja Putri Desa Sungai Alang - Siti Aisyah Solechah; Fahrini Yulidasari; Muhammad Irwan Setiawan; Ihya Hazairin Noor; Vina Yulia Anhar; Husnul Fatimah; Izal Puji Santoso (Jurnal Medika: Medika, 2026)
The South Kalimantan Provincial Health Office has demonstrated an increase target regarding iron supplementation consumption in South Kalimantan. The target for iron supplement consumption among adolescent girls in 2023 was 75% while the target in 2022 was only 54%. This figure demonstrated the increasing challenge of reducing anemia incidence among adolescent girls. A preliminary survey in Sungai Alang Village, Banjar Regency, indicated that 97% of adolescent girls in community unit 1, 2, and 3 rarely consumed iron supplements. The main factors were low knowledge levels and awareness. Most of them admitted to frequently forget to take the supplements. The environment also plays a role in these habits, including limited information media and inadequate recording by health workers. This community service activity aimed to improve adolescent girls' knowledge about anemia and iron supplements. The event was held at the Sungai Alang Village Hall on August 9, 2025, with 34 adolescent girls as the participants. The participants’ average age was 14.8±4.6 years. The campaign materials on anemia and iron supplements were delivered through lectures using PowerPoint slides and booklets. Participants' knowledge was assessed using pretest and posttest questionnaires. Participants with good knowledge increased by 14.71%, from 52.94% before the education to 67.65% afterward. The Wilcoxon test results showed a significant difference in the percentage of correct answers between pre- and post-education (p<0.05).